2022
DOI: 10.3390/jcm11216461
|View full text |Cite
|
Sign up to set email alerts
|

Mild-to-Moderate COVID-19 Convalescents May Present Pro-Longed Endothelium Injury

Abstract: Background: The SARS-CoV-2 pandemic posed a great threat to public health, healthcare systems and the economy worldwide. It became clear that, in addition to COVID-19 and acute disease, the condition that develops after recovery may also negatively impact survivors’ health and quality of life. The damage inflicted by the viral infection on endothelial cells was identified quite early on as a possible mechanism underlying the so-called post-COVID syndrome. It became an urgent matter to establish whether convale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Thus, a much larger and multi-center study with a longer followup should be conducted to confirm our findings. A more recent study demonstrates that prolonged endotheliopathy may be present even in patients with mid-to-moderate COVID-19 convalescents 36 .…”
Section: Discussionmentioning
confidence: 97%
“…Thus, a much larger and multi-center study with a longer followup should be conducted to confirm our findings. A more recent study demonstrates that prolonged endotheliopathy may be present even in patients with mid-to-moderate COVID-19 convalescents 36 .…”
Section: Discussionmentioning
confidence: 97%
“…Although previous studies had indicated that patients with COVID-19 showed gradual improvement in endothelial function during the 6month follow-up period after discharge, their endothelial function still lagged behind that of healthy individuals (40) . Another study demonstrated that at least 6 months after infection, COVID-19 survivors without other comorbidities associated with endothelial damage only showed mild evidence of endothelial dysfunction (41) . However, there were also studies indicating that the vascular damage became more severe with the progression of infection time (42) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a much larger and multi-center study with a longer follow-up should be conducted to confirm our findings. A more recent study demonstrates that prolonged endotheliopathy may be present even in patients with mid-to-moderate COVID-19 convalescence [ 36 ].…”
Section: Discussionmentioning
confidence: 99%